Activation of glucagon‐like peptide‐1 receptor inhibits tumourigenicity and metastasis of human pancreatic cancer cells via PI3K/Akt pathway. Issue 9 (15th April 2014) - Zhao, H.; Wang, L.; Wei, R.; Xiu, D.; Tao, M.; Ke, J.; Liu, Y.; Yang, J.; Hong, T.
Abstract Aims It has been reported that glucagon‐like peptide‐1 (GLP‐1) agents are associated with an increased risk of pancreatic cancer in patients with type 2 diabetes. Reports have indicated that GLP‐1 promotes pancreatic metaplasia and premalignant lesions. The aims of this study were to determine the effects of GLP‐1‐based therapy on pancreatic cancer cells. Methods Immunohistochemistry was used to investigate GLP‐1 receptor (GLP‐1R) expression in 30 human pancreatic cancer tissues. We also analysed associated clinicopathological data and each patient's prognosis. Two human pancreatic cancer cell lines were used to evaluate the in vitro effects of the GLP‐1R agonist liraglutide on cell growth, migration and invasion. Mouse xenograft models of human pancreatic cancer were established to evaluate the effects of liraglutide in vivo. Results Human pancreatic cancer tissues showed lower levels or a lack of GLP‐1R expression when compared with levels in the tumour‐adjacent pancreatic tissues. Negative GLP‐1R expression occurred more frequently in advanced tumours with larger diameters and lymphatic metastasis, and was associated with a poor prognosis. GLP‐1R activation with liraglutide inhibited tumourigenicity and metastasis of human pancreatic cancer cells in vitro and in vivo. Akt activation was dose‐dependently inhibited by liraglutide, and the PI3K inhibitors, LY294002 and wortmannin, displayed similar suppressive effects to liraglutide in human pancreatic cancer cells. Conclusions GLP‐1R activation has an antitumour effect on human pancreatic cancers via inhibition of the PI3K/Akt pathway. This finding suggests that GLP‐1‐based therapies may be beneficial, rather than harmful, in treating type 2 diabetic patients with pancreatic cancer.